Good outcome after liver transplantation for ALD without a 6 months abstinence rule prior to transplantation including post‐transplant CDT monitoring for alcohol relapse assessment – a retrospective study. (1st March 2016) - Kollmann, Dagmar; Rasoul‐Rockenschaub, Susanne; Steiner, Irene; Freundorfer, Edith; Györi, Georg Philipp; Silberhumer, Gerd; Soliman, Thomas; Berlakovich, Gabriela Andrea
Summary: Alcoholic liver disease (ALD) is the second most common indication for liver transplantation (LT). The utility of fixed intervals of abstinence prior to listing is still a matter of discussion. Furthermore, post‐LT long‐term observation is challenging, and biomarkers as carbohydrate‐deficient transferrin (CDT) may help to identify alcohol relapse. We retrospectively analyzed data from patients receiving LT for ALD from 1996 to 2012. A defined period of alcohol abstinence prior to listing was not a precondition, and abstinence was evaluated using structured psychological interviews. A total of 382 patients received LT for ALD as main ( n = 290) or secondary ( n = 92) indication; median follow‐up was 73 months (0–213). One‐ and five‐year patient survival and graft survival rates were 82% and 69%, and 80% and 67%, respectively. A total of 62 patients (16%) experienced alcohol relapse. Alcohol relapse did not have a statistically significant effect on patient survival ( P = 0.10). Post‐transplant CDT measurements showed a sensitivity and specificity of 84% and 85%, respectively. In conclusion, this large single‐center analysis showed good post‐transplant long‐term results in patients with ALD when applying structured psychological interviews before listing. Relapse rates were lower than those reported in the literature despite using a strict definition of alcohol relapse. Furthermore, post‐LT CDT measurement proved to be a useful supplementary tool for detecting alcohol relapse.